Strategi Pemanfaatan Youtube Dalam Bidang Dakwah Oleh Ulama Aceh - Arif Ramdan Sulaeman; Anhar Fazri; Fairus Fairus (Communication, 2020)
The development of information technology is very influential in the delivery of information to the public, especially social media youtube which is used to convey the message of da'wah. At this time the development of communication technology has many impacts on humans including changes in behavior, ranging from lifestyles, ways of learning, ways of shopping, and also methods in studying also use models that fit the current era. And so also with the way someone found his God, can be found via the sophistication of communication tools like today. The author in this case studies "Youtube" as an object that is now increasingly becoming a creative medium that is used by many people in conveying ideas through creativity. That way, the use of youtube by using the right strategy will provide good information for the community. This study uses descriptive qualitative methods with content analysis techniques (content analysis) using the Harold D. Lasswell approach. In this study using content analysis techniques is in-depth discussion of the contents of information and sampling is done through certain considerations, adjusted to the formulation of the problem and the ability of researchers. In this era where good and bad messages were presented and then virtualized with virtually no filtering done today. Therefore, the role of religion and of course in this case teungku dayah and santri should be able to be filters as well as perpetrators of dakwah content in terms of video message delivery channels, if not then the virtual universe will be dominated by trash content that continues to undermine the faith of the people.